An orchestra of minorities : a novel - Obioma, Chigozie, 1986- (New York : Little, Brown and Company, 2019)
In a contemporary twist on Homer's "The Odyssey," a guardian spirit recounts the tragic story of a Nigerian poultry farmer who sacrifices everything for the wealthy woman he loves.
Keywords: Farmers -- Nigeria -- Fiction; Man-woman relationships -- Fiction; Nigeria -- Fiction